2022
DOI: 10.1097/mot.0000000000001033
|View full text |Cite
|
Sign up to set email alerts
|

Use of belatacept in kidney transplantation: what's new?

Abstract: Purpose of reviewThe advent of calcineurin inhibitors have led to a significant improvement in short term outcomes after kidney transplantation. However, long term outcomes are hindered by the cardiovascular, metabolic and chronic renal toxicity associated with these agents. Belatacept is a selective T cell costimulation blocker that is approved for prevention of rejection in kidney transplantation, and has been associated with favorable cardiovascular, metabolic and renal outcomes in kidney transplant recipie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Of note, there have been reports of increased incidence of cytomegalovirus infection, slower viral clearance, and ganciclovir-resistance. Its use is contraindicated in patients seronegative to EBV given the risk of posttransplant lymphoproliferative disorder [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, there have been reports of increased incidence of cytomegalovirus infection, slower viral clearance, and ganciclovir-resistance. Its use is contraindicated in patients seronegative to EBV given the risk of posttransplant lymphoproliferative disorder [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Belatacept, a fusion protein of the Fc fragment of a human IgG1 linked to the extracellular domain of CTLA-4 [ 6 ] was engineered to overcome slightly weaker binding avidity to CD80/86 of the progenitor molecule Abatacept, which differs just by 2 amino acids. These changes increased in vitro T-cell inhibitory activity and demonstrated superior protection from allograft rejection in pre-clinical models but were limited to the i.v.…”
mentioning
confidence: 99%
“…formulation of Belatacept. Extensive clinical trials and followups have confirmed the efficacy of Belatacept for kidney transplantation [6][7][8], and the drug is often employed as a substitute or conversion agent to overcome intolerance to CNIs. Common reasons for switching include nephrotoxicity, thrombotic microangiopathy, posterior reversible encephalopathy syndrome, reducing cardiovascular risk factors, etc.…”
mentioning
confidence: 99%